The Politics of Natural Gas in the Middle East Today - Ayasreh, Emad Abdallah; Bakar, Mohamad Zaini Abu (School of Social Sciences, 2015)
A recent development in energy security studies shows the growing significance of natural gas in international relations. Natural gas security looms large in international politics, especially in conflicting regions like the Middle East. The paper delves into the increasingly significant argument that natural gas needs much more political involvement than any other source of energy, especially oil. Based on gas importers and exporters in Middle East as case studies, the paper aims to determine the weight of energy consumer and transit states in the political process with regard to the security of gas. Consequently, it examines multiple political factors that play a role in securing gas. The impact of the geopolitical factor is particularly notable. The findings show that several issues are involved in the political relations between exporting and importing states that affect the stability of gas supply and price. In summary, the paper suggests that there is an urgent need to develop a new gas security policy, especially in cases where energy exporters and importers are suffering from political and social instability in a region like Middle East.